2014
DOI: 10.1111/jog.12293
|View full text |Cite
|
Sign up to set email alerts
|

Relation between gestational weight gain and pregnancy outcomes

Abstract: To achieve a high proportion of appropriate-for-gestational-age infants, Thai pregnant women could follow our gestational weight gain recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 32 publications
4
37
0
1
Order By: Relevance
“…The management of GWG using official guidelines has been implemented globally [1,2,13,[20][21][22][23]. According to a prospective cohort study in the USA, GWG within the levels recommended by the Institute of Medicine (IOM) guidelines was associated with a decreased risk of delivering LBW babies [1].…”
Section: Discussionmentioning
confidence: 99%
“…The management of GWG using official guidelines has been implemented globally [1,2,13,[20][21][22][23]. According to a prospective cohort study in the USA, GWG within the levels recommended by the Institute of Medicine (IOM) guidelines was associated with a decreased risk of delivering LBW babies [1].…”
Section: Discussionmentioning
confidence: 99%
“…The five (24,28,35,39,52) remaining studies obtained weight and height measures from medical records. In order to categorize pre-pregnancy BMI into weight classes, 19 (15,22,23,25,27,30,33,34,38,(40)(41)(42)46,(48)(49)(50)52,54,56) studies used the World Health Organization's BMI cut-offs, and another 16 (2,7,8,18,21,26,28,29,32,35,36,43,45,47,51,53) studies used guidelines consistent with these. A further six (24,31,37,39,44,55) studies used the 1990 Institute of Medicine (IOM) (57) BMI cut-offs to determine prepregnancy BMI classifications.…”
Section: Measurement Of Pre-pregnancy Body Mass Index and Gestationalmentioning
confidence: 99%
“…In contrast, 10 studies found that multiparous women had a greater risk of excessive (18,21,35,53) and absolute (28,31,44,47,48) GWG. An additional nine studies (8,27,30,36,37,(42)(43)(44)54,56) did not report/find a significant association between parity and GWG, and a further two (15,25) studies employed an entirely nulliparous sample.…”
Section: Associations Between Gestational Weight Gain and Paritymentioning
confidence: 99%
“…Also, most previous studies have focused on GWG among overweight or obese women, whereas less attention has been given to women of normal weight or underweight women who gained excessive weight during pregnancy . Thus, the impact of pre‐pregnancy BMI and GWG has not been well studied, especially in developing countries . Moreover, few studies have investigated the association between paternal body weight and height at conception and risk of fetal macrosomia, both in developing and developed countries …”
mentioning
confidence: 99%